CAUSES OF TRAFFIC ACCIDENTS AND MEASURES TO PREVENT THEM - Muhammadjonov Azizbek; Baxromjonova Dilnoza; Azimov Sarvarbek (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: According to the information published by the government of Uzbekistan, a total of 10,001 traffic accidents occurred in Uzbekistan in 2021. More than 2,425 people were killed in road traffic accidents, and the number of injured exceeded 9,230. Most of the traffic accidents that have occurred have resulted in death or serious injury. This article talks about the causes of traffic accidents in Uzbekistan and ways to eliminate them.